2016
DOI: 10.7314/apjcp.2016.17.4.2265
|View full text |Cite
|
Sign up to set email alerts
|

The rs61764370 Functional Variant in the KRAS Oncogene is Associated with Chronic Myeloid Leukemia Risk in Women

Abstract: Background: Chronic myeloid leukemia (CML) is one of the most frequent hematopoietic malignancies in the elderly population; however, knowledge is limited regarding the genetic factors associated with increased risk for CML. Polymorphisms affecting microRNA (miRNA) biogenesis or mRNA:miRNA interactions are important risk factors in the development of different types of cancer. Thus, we carried out a case-control study to test the association with CML susceptibility of gene variants located in the miRNA machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
2
14
3
Order By: Relevance
“…After duplicate removal and subsequent title and abstract assessment, 26 articles were left for further full-text review. Based on the inclusion and exclusion criteria, 19 articles remained [ 14 32 ]. One article containing data regarding various types of cancer was treated as independent studies [ 14 ], and there were seven articles containing studies of various BRCA1 polymorphisms [ 14 , 16 , 17 , 21 , 22 , 24 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After duplicate removal and subsequent title and abstract assessment, 26 articles were left for further full-text review. Based on the inclusion and exclusion criteria, 19 articles remained [ 14 32 ]. One article containing data regarding various types of cancer was treated as independent studies [ 14 ], and there were seven articles containing studies of various BRCA1 polymorphisms [ 14 , 16 , 17 , 21 , 22 , 24 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The following information was extracted: name of first author, year of publication, country, cancer type, ethnicity, genotyping methods, source of controls, genotype distributions of cases and controls, and Hardy-Weinberg equilibrium (HWE) for controls. One of the studies only provides the percentage of each genotype, the complete data were obtained from the author [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 Moreover, there was no association with lung cancer, 24 chronic myeloid leukemia, and gastric cancer. 26 , 27 More interestingly, Yang et al found that a haplotype of the GEMIN4 gene including rs2740348 was associated with increased risk of bladder cancer. 31 In our present meta-analysis, we found that rs2740348 was significantly associated with increased risk of cancer in the general population under the recessive model (GG vs GC/CC), which agreed with the result reported by Zhu et al 35 However, this conclusion was only confirmed in a mixed population, but not in Asians and Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Uvirova et al found, in a Czech cohort, an association of this somatic variant across breast cancers, colorectal cancers, non-small cell lung cancers, and brain tumors [368]. In another study, the rs61764370 SNP was associated with a higher risk of chronic myeloid leukemia in Mexican-Mestizo women [129]. An indication of the role of HRAS polymorphisms in cancer susceptibility came from a study of an Italian gastric cancer cohort.…”
Section: Disparities At the Nuclear Genome Level And Their Role Inmentioning
confidence: 99%